Thoracic Kyphosis is Now Uncommon Amongst Children and Adolescents with Cystic Fibrosis - Barker, Nicki; Raghavan, Ashok; Buttling, Pauline; Douros, Kostas; Everard, Mark L. (Frontiers in Pediatrics, 2014)
Historically, thoracic kyphosis has been reported to be common amongst patients with cystic fibrosis. The mechanisms leading to the development of this abnormality of the chest wall are not fully understood. In order to explore the prevalence of the condition amongst children with cystic fibrosis in the early C21st and to explore factors that might be contributing to its development a retrospective cross sectional study was undertaken in a regional cystic fibrosis unit. Data was obtained from 74 children with cystic fibrosis aged 8 to 16 years attending for their annual review. Thoracic kyphosis was measured from lateral chest x-ray using an alternative Cobb Method. Lung function, disease severity and nutritional status were also recorded. Correlations between measures were explored using a multiple linear regression model. The range of Cobb angles measured was 5.4 to 44.3 degrees with thoracic kyphosis identified in only 2 subjects. There was no correlation between age and thoracic kyphosis, however, there was a significant correlation between lung function and thoracic kyphosis (p=0.004). Regression coefficient (b) was -0.26 (95% CI: -0.44, -0.08). The prevalence of thoracic kyphosis is significantly less amongst children with cystic fibrosis than previously reported. This appears likely to be associated with the overall improvements in pulmonary status. Studies of older populations may bring further understanding of increasing thoracic kyphosis in people with cystic fibrosis.